2003
DOI: 10.1086/374913
|View full text |Cite
|
Sign up to set email alerts
|

Period Changes of Two W UMa–Type Contact Binaries: RW Comae Berenices and CC Comae Berenices

Abstract: ABSTRACT.From the present times of minimum light and those collected from the literature, changes in the orbital period of the two W UMa-type contact binaries RW Com and CC Com are analyzed. The results reveal that the period changes of these two systems show the same natures, with a short-term oscillation superposed on the secular decrease. For RW Com, its period shows a secular decrease at a rate of Ϫ7 dP/dt p 0.43 # 10 days yrϪ1 . An oscillation with a periodicity of 13.7 yr and an amplitude of days is supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…The TRO theory suggests that the mass transfer from the primary to the secondary and the orbital period decreas should occur when the secondary is shrinking towards its ZAMS radius. Long-term decrease of the orbital period of a system is typical for many other W-subtype W UMa contact binaries such as RT LMi (Yang & Liu 2004), FG Hya (Qian & Yang 2005), V781 Tau , RW Com (Yang & Liu 2003), V1073 Cyg and CC Com (Yang & Liu 2003). As is well known, the observed continuous orbital period decrease of a W UMa type contact binary can be explained by a mass transfer from the primary to the secondary.…”
Section: Discussionmentioning
confidence: 65%
“…The TRO theory suggests that the mass transfer from the primary to the secondary and the orbital period decreas should occur when the secondary is shrinking towards its ZAMS radius. Long-term decrease of the orbital period of a system is typical for many other W-subtype W UMa contact binaries such as RT LMi (Yang & Liu 2004), FG Hya (Qian & Yang 2005), V781 Tau , RW Com (Yang & Liu 2003), V1073 Cyg and CC Com (Yang & Liu 2003). As is well known, the observed continuous orbital period decrease of a W UMa type contact binary can be explained by a mass transfer from the primary to the secondary.…”
Section: Discussionmentioning
confidence: 65%
“…Using an average value for the mass ratio of q = 0.5, and the values of dP = -0.446 ± 0.012 seconds and dP = 0.146 ± 0.013 seconds at the two major period changes results in dm = -5.44 ± 0.15 × 10 −6 M ⊙ for the first period change in 1984/1985, and dm = 1.78 ± 0.16 × 10 −6 M ⊙ for the second period change in 1999. As seen from the O-C diagram, these occurred rather rapidly, and even assuming the transfer occurred over as much as a couple years, these rates are still ∼10 -100 times typical mass transfer rates for W UMa systems (Yang & Liu 2003). In §4 we reported that we found a first time derivative of the period of dP/dt = 9.7 × 10 −8 for the 1984 data.…”
Section: Period Changes and Mass Transfermentioning
confidence: 68%
“…Inspecting the O-C residuals for times after the second major period change, there appears to be a slight upward trend indicating a constant period increase. Performing an error-weighted, least-squares quadratic fit to the O-C residuals, shown in Figure 2, yields a period increase of dP/dt = 3.46 ± 0.83 × 10 −7 days yr −1 , (dP/dE = 3.07 ± 0.74 × 10 −10 days cycle −1 ), which are typical values for W UMa systems (Qian 2001;Yang & Liu 2003). The implications of this trend and the other period shifts will be discussed in §5.…”
Section: Minimum Timings and O-c Diagrammentioning
confidence: 85%
See 1 more Smart Citation
“…It seems, though, that there exist activity cycles in W UMa systems (see Yang & Liu 2003, for a recent discussion). These have periods comparable to the solar case, hence should we by chance have observed V524 Mon during a "quiet" state, then there is a good chance that quick follow-up observations will find it still in this state.…”
Section: Magnetic Activitymentioning
confidence: 99%